Senior-oriented policy for the ageing society of the city of Łódź - Janiszewska, Anna (Research Papers of Wrocław University of Economics, 2018)
The article explores the issue of senior-oriented policy carried out in Łódź. Actions undertaken as part of this policy are especially crucial in contemporary times due to the major demographic changes occurring in the city. The article discusses selected demographic problems of the city, including the ageing of the society, showing their changeability in time and space. The juxtaposition of the spatial arrangement of the facilities which undertake actions benefitting the elderly with the areas of high concentration of seniors’ homes shows that the access to the former is satisfactory. On the other hand, taking into account the range of actions related to the senior-oriented policy, a unique innovativeness in regards to the issue does not appear to distinguish the city of Łódź from other cities
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 510, s. 75-89
Keywords: social policy; senior-oriented policy; ageing of society; demographic rate of ageing; Łódź; polityka społeczna; polityka senioralna; starzenie się ludności; indeks starości demograficznej